Peningkatan Minat Belajar Siswa pada Pelajaran Aqidah Akhlak melalui Pendekatan Saintifik dengan Poster Comment - Haryanti, Tutik; Andi Murniati; Abu Anwar (Jurusan Tarbiyah dan Pendidikan, 2023)
The development of the 2013 Curriculum, which is the reference for implementing learning at every level of education, is expected to be an improvement in mindset, curriculum management, deepening and expanding material, strengthening the learning process, and adjusting learning loads in order to ensure conformity between what is desired and what is produced. So in K13 the learning approach used is a scientific approach and authentic assessment, where the development of learning is by applying 21st century skills. 21st century learning is a learning transition where the developed curriculum guides schools to change the learning approach from teacher centered to student centered. This is in accordance with future demands where students must have thinking and learning skills. Therefore, this research focuses on increasing students' interest in learning about moral aqidah lessons at the madrasah tsanawiyah level. The author found that students' interest in learning at MTsN Bintan in moral aqidah lessons was very lacking. This is because teachers teach in a monotonous way where the learning that takes place is still teacher centered so that boredom arises in students during the learning process. The instruments used in this research were interviews and observations. From the results of the analysis, data was obtained that the application of a scientific approach is very appropriate for teaching moral aqidah. So there appears to be an increase in students' interest in studying moral aqidah after implementing a scientific approach using the poster comment method.